Communication and school readiness abilities of hearing-impaired preschool graduates: exploring outcomes of early intervention preschool programmes in Gauteng - Maluleke, Ntsako Precious (My University, 2017)
Background: The benefits of Early Hearing Detection and Intervention (EHDI) services on communication, cognition and socio-emotional development, including academic and vocational outcomes are well documented internationally. However, reports on EHDI services in South Africa are limited to the establishment of programmes for early detection of hearing impairments, with little focus on the outcomes of the subsequent early intervention (EI) for children diagnosed with a hearing impairment. Objective: This study explored the outcomes of two EI preschool programmes in the Gauteng province, South Africa. The current study aimed at describing the communication and school readiness abilities of hearing-impaired children who were enrolled in the EI preschool programmes, as well as to determine the factors that influenced the attainment of school readiness abilities. Methods: A descriptive research study was conducted on eight hearing-impaired children who graduated from two EI preschool programmes in the Gauteng Province. Content analysis was used to analyse the qualitative data while frequency distribution and measures of central tendency were used to analyse the quantitative data. Results: Participants were late-identified with subsequent late provision of amplification devices and commencement of EI services. Consequently, participants demonstrated sub-optimal communication and school readiness abilities for their age. Early access to EHDI services and age-appropriate communication abilities were identified as factors that influenced the attainment of age-appropriate school readiness abilities for children with a hearing impairment. Conclusion: There is a great need for the establishment of more EI programmes that will meet the unique needs of hearing-impaired children in different contexts and ensure that they also have an opportunity to develop on par with their peers with normal hearing. Further research in this area needs to be undertaken exploring similar objectives to the current study with a larger, diverse sample for improved generalisability of the findings.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Arts in Audiology in the faculty of Humanities, University of the Witwatersrand, January 2017
Keywords: Hearing disorders in children--South Africa--Gauteng; Deaf children--Education--South Africa--Gauteng